Optimalisasi Efisiensi Rantai Pasokan: Studi Perbandingan Metode Economic Order Quantity (EOQ) Dan Just-In-Time (JIT) Di PT. SSC - Dion Fahrizal H DG Pacidda; Nusran, Muhammad; Herdianzah, Yan; Fole , Asrul (Komunitas Menulis dan Meneliti (Kolibi), 2024)
This study aims to compare and analyze the application of the Economic Order Quantity (EOQ) and Just-In-Time (JIT) methods in optimizing supply chain efficiency at PT. SSC, focusing on production cost efficiency. The methodology employed includes literature review, data collection from the company, comparative analysis, and both qualitative and quantitative evaluations through a case study design. The results indicate that implementing the EOQ method resulted in cost savings of IDR 1,287,977,833, while the JIT method saved IDR 1,166,303,830, from a total inventory cost of IDR 1,581,724,881, positioning EOQ as the more optimal method for supply chain efficiency. Its impact suggests that EOQ can facilitate the company in identifying efficiency measures within the production process. In conclusion, the EOQ method demonstrates significant advantages over JIT in terms of cost savings, with recommendations for future research to involve an analysis of demand variability, lead time, batch size, and the potential integration of both methods to achieve maximum supply chain and cost efficiency.